H LITERATURE STUDY OF THE RELATIONSHIP OF PAIN INTENSITY WITH THE QUALITY OF LIFE OF OSTEOARTHRITIS ELDERLY.: HUBUNGAN INTENSITAS NYERI DENGAN KUALITAS HIDUP LANSIA OSTEOARTHRITIS - Agnica mirza; Nurhusna; Fairuz (JURNAL KEPERAWATAN UNIVERSITAS JAMBI, 2021)
Osteoarthritis merupakan penyakit yang dapat menyebabkan ketidakmampuan fisik seseorang yang menyerang semua sendi khususnya pada lansia. Gejala utama yang paling sering dirasakan penderita osteoarthritis adalah nyeri dan kekakuan pada sendi, gejala inilah yang menyebabkan pembengkakan yang dapat membatasi ruang gerak, sehingga penderita terganggu dalam melakukan aktifitas sehari-hari yang mengakibatkan penurunan kualitas hidup pada penderita osteoarthritis. Untuk mengetahui hubungan intensitas nyeri dengan kualitas hidup lansia osteoarthritis. Studi ini merupakan studi literatur yang berupa literatur review. Pencarian artikel menggunakan elektronik based, seperti Google Scholar, PubMed, dan Cambridge dengan menggunakan kata kunci Bahasa Indonesia dan Bahasa Inggris.Hal ini dilakukan untuk menemukan artikel yang sesuai dengan kriteria studi literatur kemudian dilakukan review artikel. Didapatkan 10 artikel yang diperoleh dari hasil Screening. Berdasarkan hasil analisis dari 10 artikel, didapatkan 7 artikel yang menunjukan adanya hubungan intensitas nyeri dengan kualitas hidup lansia osteoarthritis. Diharapkan bagi penelitian selanjutnya dapat melakukan penelitian yang lebih baik lagi, informasi yang diberikan jauh lebih lengkap serta artikel yang digunakan merupakan artikel yang terbaru sehingga tidak menimbulkan keragu-raguan bagi peneliti-peneliti selanjutnya Kata Kunci : Kualitas Hidup lansia, Nyeri, Osteoarthritis Abstract Osteoarthritis is a disease that can cause a person's physical disability that attacks all joints, especially in the elderly. The main symptoms that are most often felt by people with osteoarthritis are pain and stiffness in the joints, these symptoms cause swelling which can limit the patient's range of motion, and can also affect the patient's physical well-being, so that the patient is disturbed in carrying out daily activities which results in a decrease in the quality of life in the patient. patients with osteoarthritis.To determine the relationship between pain intensity and quality of life for the elderly with osteoarthritis.This study is a literature study in the form of a literature review. Search articles using electronic based, such as Google Scholar, PubMed, and Cambridge using Indonesian and English keywords. This is done to find articles that match the criteria for a literature study and then review the articles. There were 10 articles obtained from the screening results. The articles used are articles published in the 2015-2021 year. Based on the results of the analysisof 10 articles, 7 articles were found that showed a relationship between pain intensity and quality of life for the elderly with osteoarthritis. This is due to the increasing degree of pain in osteoarthritis patients, it will cause the patient to experience health problems so that it limits the patient's range of motion, decreases the patient's work ability, increases the patient's emotions and sometimes even causes osteoarthritis sufferers to experience depression and decreased mental health.It is hoped that further research can conduct better research, the information provided is much more complete and the articles used are the latest articles so as not to cause doubts for further researchers. Keywords: Quality of Life of the Elderly, Pain, Osteoarthritis